Co-design of a school-based physical activity intervention for adolescent females in a disadvantaged community: insights from the Girls Active Project (GAP) - Sara McQuinn; Sarahjane Belton; Anthony Staines; Mary Rose Sweeney (BMC, 2022)
Abstract Background Globally, adolescents' physical activity (PA) participation rates are low, particularly among lower socioeconomic groups, with females consistently the least active. The aim of this study was to co-design, with adolescent females, a school-based PA intervention in a single-sex, females-only designated disadvantaged post-primary school in Ireland. This involved using the Behaviour Change Wheel (BCW) and Public and Patient Involvement (PPI). This paper outlines the novel methodological approach taken. Methods The three stages 1) understand the behaviour, 2) identify intervention options, and 3) identify content and implementation options of the BCW guide is described. A student PPI Youth Advisory Group (YAG) (n = 8, aged 15-17) was established. Mixed-methods were used with students (n = 287, aged 12-18) and teachers (n = 7) to capture current self-reported PA levels and to identify factors influencing adolescent females' PA behaviour in their school setting. The intervention options, content and implementation options were identified through discussion groups with the YAG. The Template for Intervention Description and Replication (TIDieR) checklist was used to specify details of the intervention. Results Just 1.4% of the students in this sample reported meeting the recommended PA guidelines. Students identified having more 'time' as the strongest predictor to becoming more active in school (Mean = 4.01, 95% CI 3.91 to 4.12). Social influences, environmental context and resources, behavioural regulation, beliefs about capabilities, goals, and reinforcement emerged from the qualitative data as factors influencing PA behaviour at school. The BCW co-design process resulted in the identification of seven intervention functions, four policy categories and 21 Behaviour Change Techniques. The Girls Active Project (GAP) intervention, a peer-led, after-school PA programme was proposed. Conclusions This paper describes how the BCW, a comprehensive, evidence-based, theory-driven framework was used in combination with PPI to co-design a school-based intervention aimed to increase adolescent females' PA levels. This approach could be replicated in other settings to develop targeted behavioural interventions in populations with specific demographic characteristics.